POP-UP BOOK BERBASIS PJBL: SOLUSI KREATIF UNTUK MENINGKATKAN PEMAHAMAN SISWA DALAM MATERI SISTEM TATA SURYA - Zulfiana Rihhadatul Aisya; Dody Rahayu Prasetyo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop a Pop-Up Book learning media based on Project-Based Learning (PjBL) as a creative solution to improve students’ conceptual understanding and critical thinking skills in the topic of the Solar System. The research is driven by the issue of low student engagement and interest due to conventional, theory-based science teaching, particularly in abstract materials. The study employed a Research and Development (R&D) approach using the 4D development model: Define, Design, Develop, and Disseminate. The instruments used include expert validation sheets, student and teacher response questionnaires, observation sheets, as well as pre-test and post-test assessments. The results revealed that the Pop-Up Book based on PjBL has high validity in terms of content and design, received positive feedback from teachers and students, and effectively enhanced student comprehension, as reflected in improved post-test scores. Moreover, the media fostered active participation and collaborative learning among students. Although the dissemination phase was not conducted due to limited time and resources, the trial phase showed that the media is feasible and holds potential for broader implementation. Therefore, the PjBL-based Pop-Up Book can serve as an innovative alternative to enhance the quality of science learning at the junior high school level.